VALUASI EKONOMI DAN PERSEPSI WISATAWAN TERHADAP WISATA PANTAI M BEACH DI KABUPATEN LAMPUNG SELATAN PROVINSI LAMPUNG - Muhamad Riyan Saputra; Novi Rosanti; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
This research aimed to analyze the tourist travel costs, the factors that influence the frequency of tourist visits, the economic value of tourism, and the tourists' perceptions of M Beach. This research used a survey with a sample of 50 tourists from M Beach was selected using the accidental sampling method. The travel cost method is used to analyze the economic value, and the descriptive method with a Likert scale measuring instrument is used to analyze tourist perceptions. The determination of location was carried out purposively with the consideration that M Beach has been the best-selling tourist attraction in South Lampung Regency for the last five years. The data was collected in January 2023. The results showed the average travel costs incurred by M Beach tourists were Rp146.265,24 per individual per visit, with the highest allocation of travel costs viz consumption costs of 38,43 percent. The factors that influence tourists visits to M Beach are travel costs, distance, income, age, beach conditions, and public facilities. The total economic value of M Beach tourism is Rp10.474.348.786,00 per year. Tourists perception of M Beach in terms of 4A components (attraction, amenity, accessibility, and ancillary) has a positive perception with good criteria.Keywords: Economic value, M Beach, Perception, Travel cost